Enhancing Germination and Early Seedling Growth of Eggplant (Solanum melongena L.) Through Aeration Priming with Potassium Nitrate (KNO₃) - Putri Santika; Ilham Muhklisin; Jahrotul Laili; Leli Kurniasari; Sandile Donald Makama (Agroteknika, 2025)
Eggplant (Solanum melongena L.) is an important horticultural crop in tropical and subtropical regions. However, suboptimal seed germination and poor early seedling growth often impede successful crop establishment. Seed priming with potassium nitrate (KNO₃) is widely recognized for enhancing seed performance, but prolonged soaking in priming solutions can limit oxygen availability during imbibition, potentially inhibiting metabolic activity and reducing priming efficiency. This study aimed to evaluate the effectiveness of aerated KNO₃ priming in improving germination and seedling vigor of eggplant. A completely randomized design with seven treatments, including control, KNO₃ concentrations (0%, 1%, 2%), and priming conditions (with and without aeration), was applied. Results showed that seed priming significantly improved germination parameters, stem diameter, and dry mass. The best germination performance was observed in seeds primed with 2% KNO₃ under aeration with 88.50% germination, the highest germination rate index (23.08), and the shortest mean germination time (3.38 days). While priming did not significantly affect plant height at 35 days after planting, and the concentration of KNO₃ did not significantly affect the seedling performances, aeration significantly increased stem diameter and seedling dry mass. These findings suggest that aerated priming with 2% KNO₃ can be recommended as an effective technique to enhance germination performance and seedling vigor in eggplant.